Penerapan Standar Internasional pada Pengendalian Kebisingan di Kapal - PELAGIA, HUMAIRA (PT Yupin Felicitas Utama, 2025)
Noise is an unwanted sound, which comes from human activities or nature, and at certain levels and durations can have a negative impact on human comfort and health. On board a ship, the engine room is the main source of noise. High noise intensity and often not realized can cause serious disturbances to the crew (ABK) and cause discomfort to passengers. Therefore, soundproof efforts are needed to create a healthier and more comfortable working and traveling environment.